FLOW AND PRESSURE CONTROL OF A FIELD SPRAYER USING PID CONTROLLER - H. Karadöl (Journal of Animal and Plant Sciences, 2023)
Recently, different methods have been developed in order to increase the application efficiency of agricultural sprayer systems. The dynamic control of flow and / or pressure is performed by the proportional control of pumps or valves.The aim of the current study was to minimize the application rate error of field sprayers using the pump motor variable speed drive (VSD) of a centrifugal pump system. The flow rate and pressure control of the pump system was achieved using a Proportional Integral Derivative (PID) controller.During the tests, in the first stage, the flow rate-speed ratio was kept at a constant value to apply a constant application rate with varying ground speeds. In the second stage, the control of the system pressure was accomplished using the manually applied disturbing effects on the system. In the final stage, the flow rate of a spray nozzle was controlled by Pulse Width Modulation (PWM) depending on the speed at different constant pressure values. In flow control test, absulute percentage error of application rate in only six out of 150 measurements were higher than 10% which is acceptable application rate error at varying ground speeds from 6 to 10 km h-1. In pressure control tests, it was observed that the controller moved the system pressure back to the set value within 2-3 seconds after a disturbance applied. The system was able to control the nozzle flow rates between 50% and 100% by changing the duty cycle of the signal applied to the solenoid valve at the nozzle inlet during the PWM spray tests. Further investigation is required to test the observation in the current experiment on field sprayers to improve the efficiency of constant and variable rate or PWM applications.
Keywords: PID; Flow based control; Sprayers; Variable rate application